Introduction of Feed Technology in Support Development of Beef Cattle - Elly, Femi Hadidjah; Salendu, Artise H.S.; Lomboan, Agustinus; Poli, Zulkifli; Rintjap, Anneke K. (International Journal of Environment, Agriculture and Biotechnology, 2021)
The problem of beef cattle breeding developed by rural communities was done traditionally. Farmers use land under coconut for raising beef cattle, but feed consumed was low quality grass. This condition has an impact on low productivity of beef cattle so that selling price was also low. This research was conducted with the aim of analyzing potential for forage development in Bolaang Mongondow Regency. The research method used was a survey, with determination of location is by purposive sampling, which was village that has most cattle population. Data collected were primary and secondary. Respondents were determined by purposive sampling, namely 30 farmers who use land under a coconut tree. Data were analyzed descriptively and using IDD analysis. PMSL Value 21396.39, KPPTR(SL) 12043.76, PMKK Value 107557.8, KPPTR (KK) 87438.8. The carrying capacity index value of 1.40 shows that based on potential of existing land, real population can still be increased up to 1.40 times. In conclusion, development of land under a coconut can be done through introduction of forage. Suggestion, forage is developed by considering its quality.